Risk factors of sensory hearing loss in nasopharyngeal carcinoma patients obtaining conventional radiotherapy - Odhi Anggani; Sagung Rai Indrasari; Feri Trihandoko; Anisa Haqul Khoiria; Ashadi Prasetyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Previous studies proven that cochlear hair cells’ death plays an important role in sensorineural hearing loss due to radiation exposure. Other studies compared the differences between the impact of conventional radiotherapy (CRT) and intensity modulated radiation therapy (IMRT) on hearing loss in patients with nasopharyngeal carcinoma. Although, few differences found in some clinical manifestation, however no statistical analysis had been carried out. The aim of study was to evaluate the risk of sensory hearing loss in nasopharyngeal carcinoma patients who received CRT compared to IMRT. A case control study was performed on nasopharyngeal carcinoma patients who received radiotherapy at Dr. Sardjito General Hospital, Yogyakarta. The result of DPOAE between NPC patients who received CRT and IMRT was compared in this study. Statistical analysis was performed using chi square test and multivariate analysis. The result showed that patients who received CRT significantly altered the risk for sensory hearing loss in the contralateral ear as much as 11.2 times according to the multivariate analysis (CI 95%: 2.2 – 56.6; p=0.004). In conclusion, the risk of sensory hearing loss in patients with nasopharyngeal carcinoma who received CRT is a greater compared to IMRT.